Application of an intragenic genomic probe to genetic counselling for haemophilia B in the west of Scotland. Issue 6 (December 1985) - Connor, J M; Pettigrew, A F; Hann, I M; Forbes, C D; Lowe, G D; Affara, N A
Abstract : Total ascertainment revealed 28 families with haemophilia B in the west of Scotland (prevalence 1/26 870 males). In 12 of these families more than one person was affected and 26 living obligate carriers were identified and tested. Of these, 42% were heterozygous for a DNA polymorphism recognised by a factor IX genomic probe. No recombination was observed in 11 phase known and four phase unknown informative meioses. Definitive genetic counselling was possible for 14 of 42 females at risk, 11 could not be traced, in 10 the probe was not informative, and in seven paternal absence prevented interpretation. Linkage disequilibrium was apparent for this restriction fragment length polymorphism and haemophilia B in the west of Scotland.